2021
DOI: 10.3906/sag-2001-231
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the National Institutes of Health Chronic Prostatitis Symptom Index questionnaire in the Turkish Population

Abstract: Background/aim To develop the first Turkish version of the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) questionnaire and to investigate its validity and reliability in men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and healthy controls. Material and methods A total of 204 patients, 116 CP/CPPS and a control group which consisted of 88 healthy individuals were included in this prospective study. The NIH-CPSI form was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Chronic prostatitis is a disease of young adults under 50 years [8], [40], [41] characterized by voiding symptoms, genitourinary pain, and often sexual dysfunction, that may lead to impaired sexual and reproductive health [7], [8], [42], [43], [44], such as erectile dysfunction and premature ejaculation [42], [45], [46], [47], [48]. Erectile dysfunction is 3.6 times more common in men with chronic prostatitis symptoms [49], and up to 35% of patients with chronic prostatitis experience erectile dysfunction [48].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic prostatitis is a disease of young adults under 50 years [8], [40], [41] characterized by voiding symptoms, genitourinary pain, and often sexual dysfunction, that may lead to impaired sexual and reproductive health [7], [8], [42], [43], [44], such as erectile dysfunction and premature ejaculation [42], [45], [46], [47], [48]. Erectile dysfunction is 3.6 times more common in men with chronic prostatitis symptoms [49], and up to 35% of patients with chronic prostatitis experience erectile dysfunction [48].…”
Section: Discussionmentioning
confidence: 99%
“…Since its appearance in 1999, 10 the NIH CPSI has been a versatile tool that allows, in an agile way, for the characterization of the experience of prostatitis‐like symptoms 10 . Some researchers suggest that the impact of pain on life quality is even more significant than the relevance of urinary symptoms or the location of the pain 1,7 . Furthermore, in urology, self‐filling questionnaires are widely accepted for patients' initial diagnosis and assessment 30 …”
Section: Discussionmentioning
confidence: 99%
“…Prostatitis is a highly prevalent disease worldwide, 1,2 about 15% of men under 50 years will experience prostatitis symptoms at some point in their lives, 1,2 which is a similar prevalence to chronic diseases such as diabetes 1,3 . It has been suggested that due to high prevalence of prostatitis, the often ambiguity of symptoms, debatable diagnostic methods and the argument that few investigations have been developed; it has been considered an enigmatic disease 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations